Pertumbuhan dan Kadar Albumin Ikan Gabus (Channa striata) yang Diberi Pakan Keong Mas dengan Dosis Berbeda - Ilyas, Sulastri; Kurnia, Agus; Hamzah, Muhaimin (Universitas Halu Oleo, 2018)
This study aimed to determine the optimum dose of apple snail to improve the growth and albumin content of snake head fish. The fish were reared in 9 plastic container (diameter of 50 cm and height 55 cm). All container were filled with freshwater 10 L in each container filled with 5 fish (initial weight : 32,3 ± 1,7g). Three doses of apple snail : 10% of fish biomassa (treatment A), 15% of fish biomassa (treatment B) and 20% of fish biomassa (treatment C) fed to the fish for 45 days of rearing. The fish fed with apple snail in three times a day (08.00, 12.00 and 16.00). The results showed that the fish fed with different dosage of apple snail were not significantly different in weight gain, spesific growth rate (SGR), feed conversion ratio (FCR) feed eficiency (FE) and survival rate (SR) of snake head fish. The weight gain of fish was ranged between 19.55 ± 1.78-25.60 ± 2.10 g, SGR of fish was ranged between 1.05 - 2.23%, FCR of fish was ranged 4.3 - 6.19 , FE of fish was ranged between 16.58 - 23.30%. The highest of feed consumption was found fish fed with 15% and 20% of apple snail. While, the highest of albumin content was found in the fish fed with 15% of apple snail dosage.Keywords : growth, albumin, snake head fish, Channa striata, apple snail